The Job hopping among Generation Z is influenced by toxic workplaces and bullying, mediated by emotional exhaustion and moderated by openness to experience. (International Journal of Economics and Management Research, 2026)
This study investigates the impact of a toxic work environment, bullying behavior, and emotional exhaustion on the tendency for job hopping among Generation Z in Banyumas Regency. Data were obtained from 100 respondents through questionnaires and interviews, using a Likert scale of 1-5 and analysis using SEM-PLS. The results showed that a toxic work environment, workplace bullying, and emotional exhaustion significantly affect job hopping. Emotional exhaustion acts as a mediator between workplace bullying and job hopping, while openness to experience moderates this relationship. Recommendations for organizations include implementing employee welfare programs and stress management training to reduce the negative impacts of the work environment. This study highlights the importance of considering personal factors and personality characteristics in understanding employee behavior related to emotional exhaustion and job hopping. The PLS SEM analysis shows good validity and reliability, with hypothesis testing using the bootstrapping technique indicating significant effects between the variables tested. The gender variable did not significantly affect job hopping, whereas other variables such as a toxic environment, workplace bullying, emotional exhaustion, and openness to experience had significant impacts. This study contributes to the understanding of factors influencing job hopping behavior among Generation Z and offers new directions for further research on the role of openness to experience in the relationship between emotional exhaustion and job hopping.